Diffusion and effectiveness of TeleCTG in maternal care at primary health centers - Adzka Fahma Rodliya; Dwi Agustian; Siska Bradinda Putri Sudirman; Siti Hanisa Khaira (Berita Kedokteran Masyarakat, 2026)
Purpose: Digital health innovations like telecardiotocography (TeleCTG) are promoted to strengthen maternal services in primary care, yet their diffusion and effectiveness within Indonesia’s health system remain underexplored. This study analyzed the diffusion of TeleCTG and maternal service outcomes at a primary health center. Methods: A concurrent embedded mixed- methods design was used. Qualitative data were obtained through in-depth interviews with nine stakeholders and were analyzed thematically using Rogers’ diffusion of innovation framework. Quantitative data were obtained from a retrospective cohort of 78 pregnant women (34 TeleCTG exposure; 44 standard care). Bivariate analysis used Chi-square or Fisher’s exact test, and multivariable analysis used a risk-ratio framework with log-binomial or modified Poisson regression, with robust variance estimates when sparse data limited convergence. Results: Four themes emerged from the qualita- tive analysis: innovation characteristics, communication channels, time, and social system. TeleCTG was perceived as advantageous for real-time monitoring and referral support, but its diffusion remained constrained by dependence on governance and policy. Quantitatively, no statistically significant adjusted association was observed between TeleCTG use and infant mortality, cesarean section, low APGAR score at 5–10 minutes, or planned early referral. Sparse events limited estimation for some outcomes, suggesting that TeleCTG functioned more as a service-support tool than as a determinant of measurable clinical outcomes in this sample. Conclusion: Health system readiness, not technology alone, drives TeleCTG adoption. Primary care managers should integrate TeleCTG workflows; district authorities should streamline procurement; and national policymakers should issue adoption guidelines.